2016
DOI: 10.1507/endocrj.ej16-0194
|View full text |Cite
|
Sign up to set email alerts
|

Lower body weight and BMI at birth were associated with early adiposity rebound in 21-hydroxylase deficiency patients

Abstract: 21-HYDROXYLASE DEFICIENCY (21-OHD) isthe most common type of congenital adrenal hyperplasia (CAH). Its major clinical manifestations are adrenal crisis, virilization of external genitalia, short stature, and infertility due to adrenal androgen excess. A major part of the treatment for 21-OHD is glucocorticoid therapy, which reduces the excessive production of androgen and its metabolites by the adrenal gland [1][2][3].Obesity and metabolic syndrome during young adulthood are of serious concern for 21-OHD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…In general, there were no correlations between serum testosterone or FAI and timing of AR, and women with PCOS were hyperandrogenic compared with controls regardless of the timing of AR. Despite this finding, androgen levels during childhood have been shown to be associated with the timing of AR, since children with premature adrenarche or 21-hydroxylase deficiency do have early AR [28, 29]. Regarding 21-hydroxylase deficiency, one study hypothesized that low birth weight with concomitant excess androgen exposure during the fetal and perinatal periods may contribute to timing of AR, whereas in cases of premature adrenarche it is thought that early growth acceleration leads to obesity that may results into premature adrenarche [28, 29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, there were no correlations between serum testosterone or FAI and timing of AR, and women with PCOS were hyperandrogenic compared with controls regardless of the timing of AR. Despite this finding, androgen levels during childhood have been shown to be associated with the timing of AR, since children with premature adrenarche or 21-hydroxylase deficiency do have early AR [28, 29]. Regarding 21-hydroxylase deficiency, one study hypothesized that low birth weight with concomitant excess androgen exposure during the fetal and perinatal periods may contribute to timing of AR, whereas in cases of premature adrenarche it is thought that early growth acceleration leads to obesity that may results into premature adrenarche [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this finding, androgen levels during childhood have been shown to be associated with the timing of AR, since children with premature adrenarche or 21-hydroxylase deficiency do have early AR [28, 29]. Regarding 21-hydroxylase deficiency, one study hypothesized that low birth weight with concomitant excess androgen exposure during the fetal and perinatal periods may contribute to timing of AR, whereas in cases of premature adrenarche it is thought that early growth acceleration leads to obesity that may results into premature adrenarche [28, 29]. To support this, previous studies have revealed high testosterone levels in obese adolescent girls [27], but unfortunately, data on serum testosterone levels in adolescence were not available in our study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of CUG for later neurodevelopment favors the promotion of rapid growth in infants born preterm; however, CUG in infants born at term (normal or low birth weight for gestation) is likely to have adverse effects on long-term health ( 75 ). Children born with low birth weight or SGA have an increased risk for non-communicable diseases (NCDs) such as type 2 diabetes and cardiovascular disease later in life, as illustrated by the concept of Developmental Origins of Health and Disease (DOHaD) ( 76 , 77 , 78 , 79 , 80 ). Poor maternal nutritional status or smoking during pregnancy are major causes of intrauterine growth restriction ( 76 , 77 ).…”
Section: Catch Up Growthmentioning
confidence: 99%
“…Interestingly, adiposity rebound, consisting in the re-increase of BMI after its nadir, occurs significantly earlier in CAH patients than non-affected children, possibly predicting development of obesity (15, 34). In a recent study (35) on 29 classic CAH patients identified by neonatal screening and followed-up for at least 10 years, multivariate regression analysis identified lower BMI at birth as an independent predictor of early adiposity rebound, thus suggesting that early alterations in fetal life may predispose to the development of metabolic problems.…”
Section: Traditional CV Risk Factorsmentioning
confidence: 99%